THE INFLUENCE OF STORE ASSOCIATES ON BOOK PURCHASE DECISIONS AT GRAMEDIA BOOKSTORE LIPPO PLAZA KENDARI - Azis Muthalib, Dzulfikri; Conny, Conny (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to determine and explain the influence of store associates on book purchase decisions at Gramedia Bookstore Lippo Plaza Kendari. The population in this study consists of all customers at Gramedia Bookstore Lippo Plaza Kendari. The sample for this study is 60 customers from the bookstore. This research employs simple linear regression analysis. The results indicate that store associates have a positive and significant influence on book purchase decisions at Gramedia Bookstore Lippo Plaza Kendari. An increase in the quality of store associates positively and significantly affects the improvement of book purchase decisions at Gramedia Bookstore Lippo Plaza Kendari. This finding shows that well-performing store associates contribute to the enhancement of purchase decisions.